2016
DOI: 10.1080/15384047.2016.1219814
|View full text |Cite
|
Sign up to set email alerts
|

The long noncoding RNA H19 promotes cell proliferation via E2F-1 in pancreatic ductal adenocarcinoma

Abstract: H19 is a long noncoding RNA differentially expressed in many tumors and participates in tumorigenesis. This study aimed to investigate the expression and function of H19 in pancreatic ductal adenocarcinoma (PDAC). Pure malignant cells were isolated from frozen sections of 25 PDAC cases by laser captured microdessection, and H19 expression level was detected by qRT-PCR. Knockdown and overexpression were employed to manipulate H19 levels in pancreatic cancer cells, then cell viability, proliferation, apoptosis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 29 publications
3
57
0
Order By: Relevance
“…For example, Ma et al reported that H19 promotes proliferation of pancreatic ductal adenocarcinoma cells [24]. Yang et al showed that overexpression of H19 increases cell proliferation and decreases apoptosis of gastric cancer cells [25].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Ma et al reported that H19 promotes proliferation of pancreatic ductal adenocarcinoma cells [24]. Yang et al showed that overexpression of H19 increases cell proliferation and decreases apoptosis of gastric cancer cells [25].…”
Section: Discussionmentioning
confidence: 99%
“…The lncRNA H19 is an estrogen‐regulated gene whose expression is suppressed in adult liver . Aberrant expression of H19 has been associated with various cancers . H19 is also up‐regulated in BDL mice .…”
Section: Resultsmentioning
confidence: 99%
“…In accordance with the previous studies, H19 downregulation was found to inhibit cell proliferation and invasion of breast cancer cells, indicating that H19 acted as an oncogene and upregulation of H19 played a crucial role in breast cancer. Consistently, H19 was highly expressed and played oncogenic role by promoting cell proliferation in cervical cancer and pancreatic ductal adenocarcinoma . Thus, H19 may act as a potential biomarker and therapeutic target for breast cancer progression and diagnosis.…”
Section: Discussionmentioning
confidence: 99%